Upgrading of pyrolysis bio-oil to fuel over supported nanomaterials âA review - Yasir, M. (Trans Tech Publications Ltd, 2014)
Upgrading of bio-oil obtained from pyrolysis of biomass is one of the most attractive ways to produce fuel both in technological and economical aspect. Development of cost-effective, long life, and highly active catalyst is a major challenge in this concern. Addition of support material to the nanocatalyst not only increases the life span of the catalyst but also offers more active sites as well as reduces the cost by lowering the amount of active metal used. Moreover, selection of appropriate support favors efficient dispersion of the active phase. The main focus of this review article is to look into the development of supported nanocatalysts in the past few decades and comparing catalytic performance and deactivation rate of catalysts in the upgrading of bio-oil to produce a value-aided and efficient transportation fuel. Overall, appreciable work has been done to improve the hydrodeoxygenation reaction using different nanosized rare earth metal support materials with enhanced catalytic efficiency and finally need to be implemented in industries for upgrading of pyrolysis bio-oil. Â© 2014 Trans Tech Publications, Switzerland.